Історичні форми релігійного лідерства на основ іудейських традицій - Москаленко, Л. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2009)
У статті досліджується інститут релігійного лідерства на основі іудейських традицій і його історичні форми: першосвященство, пророчество, мудречество і рабинат. Автор вивчає релігійний акцент діяльності кожної із форм лідерства, їх функціонування і основні механізми впливу на адептів. In the article of investigates the institute of religious leadership on the basis of Judaic traditions as well as the historical forms of the leadership: pontificy, prophecy, pharisaism, and rabbinate. The author makes an attempt to arrange the religious aspect of the activity of each form of the leadership, to learn their functions and basic mechanisms of the influence to adherents. In the article investigates the institute of religious leadership on the basis of Judaic traditions as well as the historical forms of the leadership: pontificy, prophecy, pharisaism, and rabbinate. The author makes an attempt to arrange the religious aspect of the activity of each form of the leadership, to learn their functions and basic mechanisms of the influence to adherents.